2014
DOI: 10.1638/2013-0281r1.1
|View full text |Cite
|
Sign up to set email alerts
|

PHARMACOKINETICS OF SINGLE DOSE ORAL MELOXICAM IN BOTTLENOSE DOLPHINS (TURSIOPS TRUNCATUS)

Abstract: The objective of this study was to investigate the pharmacokinetics of meloxicam in bottlenose dolphins (Tursiops truncatus). Ten adult bottlenose dolphins were used for the study. Each animal received a single oral dose of meloxicam at 0.1 mg/kg. Two to seven serial blood samples were collected per animal, at one of fourteen time points between T = 0 and T = 240 hr. Complete blood count and serum chemistry analysis were performed prior to drug administration, as well as at the final time point for each indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In contrast, the animal in this case had a total treatment period of 14 days and a partial remission in excess of 2400 days. The reason for this is unclear and while it is assumed that cetaceans have a system of cyclooxygenases similar to mammals, the role of specific mediators in the inflammatory cascades are yet to be defined and are worthy of further research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the animal in this case had a total treatment period of 14 days and a partial remission in excess of 2400 days. The reason for this is unclear and while it is assumed that cetaceans have a system of cyclooxygenases similar to mammals, the role of specific mediators in the inflammatory cascades are yet to be defined and are worthy of further research.…”
Section: Discussionmentioning
confidence: 99%
“…However, piroxicam, as a non‐selective COX inhibitor, also inhibits the COX1 enzymes that are responsible for the maintenance of normal cellular function, which can lead to renal toxicity and gastric ulceration and although various NSAIDs have been administered to cetaceans, these animals appear to be particularly sensitive to the associated side effects, particularly gastrointestinal ulceration . A recent pharmacokinetic study showed that the elimination half‐life of meloxicam in bottlenose dolphins ( Tursiops truncatus ) was significantly longer than in other species and hence caution is required with its long‐term use. The use of piroxicam in bottlenose dolphins has not been documented and poses an additional risk given the non‐selective nature of this NSAID.…”
mentioning
confidence: 99%